Keys to first Corinthians : revisiting the major issues - Murphy-O'Connor, J. (Jerome), 1935-2013 ([CRKN ebooks]., 2009)
Essential reading for students and scholars of First Corinthians, this volume brings together 16 influential journal articles on the Pauline epistle from a leading expert in the field. Professor O'Connor provides postscripts to each article, engaging with the continuing debates on issues raised.